THE SCALAR AND TENSOR GLUEBALL MASSES IN LATTICE GAUGE-THEORY - Teper, M (1987)
We calculate 0+ and 2+ correlation functions using an improved method. On small physical volumes we reproduce the result, m(0+)≈m(2+), recently obtained by other methods. However, we also obtain evidence that for larger physical volumes the 2+ is heavier than the 0+: m(2+) m(0+)≈ 5 3. © 1987.